Evaluation of calendar lifetime’s influence of engines АШ-62ИР on their technical state - Карпов E. H.; Сикорский, Е. А.; Якушенко A. C. (Proceedings of National Aviation University (archive), 1999)
Motivation of need of the work directed for the extension of calendar lifetime of aviation engines АШ-62ИР within their time between overhaul is brought. Main defects are considered, which can appear during long keeping of engines. Stand description for testing an engine АШ-62ИР is brought, as well as systems for registration of the parameters of an engine work are required for determinations of its technical condition